OP73 Systems science for caribbean health: the development of a system dynamics model for guiding policy on diabetes in a resource limited setting. (2nd September 2017) - Guariguata, L; Guell, C; Samuels, TA; Rouwette, EAJA; Woodcock, J; Hambleton, IR; Unwin, N
Abstract : Background: Type 2 diabetes (T2DM) is a major cause of morbidity and mortality in the Caribbean and a threat to development. Halting its rise by 2025, a WHO target, requires interventions addressing the determinants of unhealthy diet and physical inactivity. The objective of this project is to engage with stakeholders in the development of a system dynamics (SD) simulation model on the effect of different policy interventions on diabetes prevalence and mortality in the Caribbean. Methods: Following SD methodology, we used a mixed methods approach to combine interviews (n=13) with stakeholders from multiple sectors across four countries (Barbados, Belize, Jamaica, and Saint Vincent and the Grenadines) with existing data on regional NCD policy and quantitative evidence. An additional twenty-two interviews from stakeholders in 7 Caribbean countries that were conducted as part of an ongoing policy evaluation study were also reviewed. Participants were sampled from existing contacts and their referrals. Analysis was guided by iterative thematic analysis using a grounded approach. A subgroup of stakeholders participated in a group model-building workshop to develop causal maps on the determinants of physical inactivity, unhealthy diet and effective healthcare delivery in the Caribbean. Data from the qualitative and quantitative reviews were applied to further develop the causal structures. Results: Stakeholders reinforced the need for upstream interventions including the provision of a healthy food environment and sustainable urban development facilitating active living, supported by fiscal incentives (subsidies) and disincentives (taxes). Stakeholders emphasised car-based development as a major driver of physical inactivity including a lack of infrastructure for active transport, a high social regard for car usage and a lack of social support for physical activity. Unhealthy diet, according to stakeholders, was driven by changing social structures in the home, the marketing and distribution of highly processed foods, and limited access to locally produced fresh fruits and vegetables. The causal maps are serving as the basis for a stakeholder-driven policy simulation model that will be validated against quantitative evidence. Conclusion: The interconnectedness of diabetes determinants highlights the importance of a multi-sectoral response and a systemic approach to decreasing the diabetes burden. The simulation model aims to aid Caribbean policymakers in evaluating the potential impact of different policy options on future diabetes prevalence and mortality. The overall utility of this approach to stakeholder engagement and option appraisal will be assessed and developed further for use in other resource-constrained settings.